Analysis of per- and polyfluoroalkyl substances (PFAS) extraction from contaminated firefighting materials: Effects of cleaning agent, temperature, and chain-length dependencies - Sixten Dahlbom; Fanny Bjarnemark; Björn Nguyen; Sarunas Petronis; Tove Mallin (Emerging Contaminants, 2024)
This investigation delves into the extraction dynamics of 22 per- and polyfluoroalkyl substances from PFAS contaminated firefighting materials. Two distinct test sets were executed: one contrasting a commercial product with water following an elaborate decontamination procedure, and the other assessing seven washing agents on materials from firefighting installations, with one agent examined at 22 °C and 50 °C. A general tendency for improved desorption at the higher temperature was observed. Furthermore, a discernible influence of the cleaning agent's pH on the extraction of specific PFAS species was observed, elucidating the role of chemical environment in the extraction process. PFAS rebound was studied for a period of up to 157 days, this unveiled a gradual escalation in PFAS22 levels, indicative of a protracted desorption mechanism. Intriguingly, PFAS with abbreviated carbon chains (C4–C6) exhibit superior desorption efficiency compared to their elongated congeners, suggesting a chain-length-dependent decontamination potential. A comparative scrutiny between a commercially available cleaning product, featuring multiple washing and flushing steps, and a water-only treatment regimen underscores the potential efficacy of the former. This exhaustive investigation furnishes nuanced insights into PFAS extraction complexities, offering a foundation for informed decontamination strategies.